Evaluation of liaison interpreting in university education: Game of Thrones – How professionally does Missandei act? - Limbach, Christiane; Stender, Alice (Glottodidactica, 2018)
This article aims to present a didactic teaching proposal, which broaches the issue of evaluation of liaison interpreting. An interpreting scene in the popular series Game of Thrones, in whose third season the slave Missandei serves as a negotiating interpreter, will serve as a live demonstration. On the basis of the evaluation criteria elaborated by Kautz (2002), this scene will be examined and analysed in a plenary session, to enable students to form a clear idea about how negotiation interpreting can look in practice, what difficulties can arise, what solutions can be found and what strategies can be adopted. The subsequent discussion serves as a starting point for further reflections about professional ethics, codes of ethics, the neutrality of the interpreter, etc. This teaching proposal has attracted wide interest and its didactic could all be more than achieved.